2019
DOI: 10.1242/jeb.194332
|View full text |Cite
|
Sign up to set email alerts
|

Loss of angiotensin-converting enzyme-related (ACER) peptidase disrupts behavioural and metabolic responses to diet in Drosophila melanogaster

Abstract: Drosophila Acer (Angiotensin-converting enzyme-related) encodes a member of the angiotensin-converting enzyme (ACE) family of metallopeptidases that in mammals play roles in the endocrine regulation of blood homeostasis. ACE is also expressed in adipose tissue, where it is thought to play a role in metabolic regulation. Drosophila ACER is expressed in the adult fat body of the head and abdomen and is secreted into the haemolymph. Acer null mutants have previously been found to have reduced night-time sleep and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 75 publications
(110 reference statements)
2
18
0
Order By: Relevance
“…Some ACE-like factors have been shown to be affected by ACE-Is including Acer and Ance (Williams et al, 1996;Houard et al, 1998) however, the targets of either protein have yet to be identified. Acer null mutants have also been shown to exhibit disruptions in night-time sleep and sleep fragmentation (Carhan et al, 2011) as well as altered behavioural and metabolic responses to diet (Glover et al, 2019). However, these flies develop normally to adulthood, suggesting that major developmental or signaling pathways have not been affected.…”
Section: Discussionmentioning
confidence: 99%
“…Some ACE-like factors have been shown to be affected by ACE-Is including Acer and Ance (Williams et al, 1996;Houard et al, 1998) however, the targets of either protein have yet to be identified. Acer null mutants have also been shown to exhibit disruptions in night-time sleep and sleep fragmentation (Carhan et al, 2011) as well as altered behavioural and metabolic responses to diet (Glover et al, 2019). However, these flies develop normally to adulthood, suggesting that major developmental or signaling pathways have not been affected.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that Gbs-76A contributes to the regulation of Lipin phosphorylation. Female Lipin DNLS flies less efficiently down-regulate Acer, a gene that is involved in glycogen metabolism as well (49) and they less efficiently up-regulate glycolytic enzymes. This suggests that, similar to the males, females cannot make efficient use of energy reserves, although lipolytic enzymes are not as much affected in females as they are in males.…”
Section: Discussionmentioning
confidence: 99%
“…Acer mutants of Drosophila have reduced glycogen stores. It is, therefore, somewhat surprising that these mutants exhibit slightly increased starvation resistance (49). Thus, reduced down-regulation of Acer in the Lipin DNLS mutant may contribute to the starvation sensitivity of the mutant.…”
Section: Genes Involved In Energy Homeostasismentioning
confidence: 99%
“…Based on the above studies, ACE, which was significantly upregulated in our results, plays a key role in the RAS pathway. A series of studies show that ACE is related to glucose and lipid metabolism (Vaughan et al, 2016;Glover et al, 2019). In addition, ACE modulates behavioral and metabolic responses to diet in Drosophila melanogaster (Glover et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies show that ACE is related to glucose and lipid metabolism (Vaughan et al, 2016;Glover et al, 2019). In addition, ACE modulates behavioral and metabolic responses to diet in Drosophila melanogaster (Glover et al, 2019). Moreover, ACE may alter anxiety-like behavior (Wang L.A. et al, 2018) and cognitive ability (Gamba et al, 2019) by mediating the RAS.…”
Section: Discussionmentioning
confidence: 99%